DEVELOPING STRATEGIES FOR IMPROVING PERFORMANCE OF KERALA FINANCIAL CORPORATION - K.S.Rajeev and Suresh Subramoniam (REVIEW OF SOCIAL SCIENCES, 2014)
Kerala Financial Corporation (KFC) is a financial institution incorporated on 01.12.1953 under the State Financial Corporation Act of 1951. KFC plays an important role in the economic development of the State and also provide employment opportunities in the state by giving financial assistance to Micro Small and Medium Enterprises (MSME). The objective of SWOT analysis is to formulate strategies using, Threat Opportunity Weakness Strength (TOWS) matrix, Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) for improving the performance of Kerala Financial Corporation. It is also planned to achieve by maximizing gains from the existing strengths, reducing current weaknesses, exploiting the available opportunities to the best possible extent and also by minimizing threats. The study is about the development of TOWS matrix, generation of Internal and External factor analysis summary and formulation of various strategies for improving the performance and overall functioning of KFC.